Next Generation Sequencing Analysis and its Benefit for Targeted Therapy of Lung Adenocarcinoma - Kulda, Vlastimil; Polivka, Jiri; Svaton, Martin; Vanecek, Tomas; Buresova, Marcela; Houfkova, Katerina; Bagheri, Mahyar Sharif; Knizkova, Tereza; Vankova, Bohuslava; Windrichova, Jindra; Macan, Petr; Babuska, Vaclav; et al. (Cancer genomics & proteomics, 2023)
BACKGROUND/AIM: Targeted therapy has become increasingly important in treating lung adenocarcinoma, the most common subtype of lung cancer. Next-generation sequencing (NGS) enables precise identification of specific genetic alterations in individual tumor tissues, thereby guiding targeted therapy selection. This study aimed to analyze mutations present in adenocarcinoma tissues using NGS, assess the benefit of targeted therapy and evaluate the progress in availability of targeted therapies over last five years. PATIENTS AND METHODS: The study included 237 lung adenocarcinoma patients treated between 2018-2020. The Archer FusionPlex CTL panel was used for NGS analysis. RESULTS: Gene variants covered by the panel were detected in 57% patients and fusion genes in 5.9% patients. At the time of the study, 34 patients (14.3% of patients) were identified with a targetable variant. Twenty-five patients with EGFR variants, 8 patients with EML4-ALK fusion and one patient with CD74-ROS1 fusion received targeted therapy. Prognosis of patients at advanced stages with EGFR variants treated by tyrosine kinase inhibitors and patients with EML4-ALK fusion treated by alectinib was significantly favorable compared to patients without any targetable variant treated by chemotherapy (p=0.0172, p=0.0096, respectively). Based on treatment guidelines applicable in May 2023, the number of patients who could profit from targeted therapy would be 64 (27.0% of patients), this is an increase by 88% in comparison to recommendations valid in 2018-2020. CONCLUSION: As lung adenocarcinoma patients significantly benefit from targeted therapy, the assessment of mutational profiles using NGS could become a crucial approach in the routine management of oncological patients.
Keywords: nádory plic; adenokarcinom plic; Adenocarcinoma of Lung; Lung Neoplasms; Humans; ErbB Receptors; targeted therapy; mutace; lung adenocarcinoma; lidé; tyrosinkinasy; NGS; erbB receptory; tyrosinkinasové receptory; protoonkogenní proteiny; Protein-Tyrosine Kinases; Receptor Protein-Tyrosine Kinases; Proto-Oncogene Proteins; vysoce účinné nukleotidové sekvenování; High-Throughput Nucleotide Sequencing; Mutation; prognosis